Joan of Navarre - Woodacre, Elena, author.
1 online resource.
Keywords: "This book is the first full-length biography of Joan of Navarre, a fascinating royal woman who became duchess of Brittany and queen consort of England through her two marriages in 1386 and 1403 respectively. Joan of Navarre is a useful resource for all students and scholars interested in queenship studies, women's history, and European politics during the later Middle Ages"--